IMPACT OF BULGARIA’S AGRICULTURAL POLICY AND STRUCTURAL CHANGES IN AGRICULTURE AND LAND RELATIONS - AN INTEGRAL PART OF THE CAP - Teodora STOEVA; Violeta DIRIMANOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Land relations are complex public relations arising on the basis of land use as an indispensable means of production in the agricultural sector. In the last three decades, the dynamics in development and the specifics of the complex processes related to the improvement of land relations in Bulgaria have reshaped public relations and led to significant institutional changes in the national economy, in particular in the agriculture in Bulgaria. A main factor for the dynamic changes in Bulgarian agriculture and land relations are the historical changes in the social model of society. The implementation of the Community agricultural policy after 2007 has brought new dynamic changes to the business environment in which this primary Bulgarian industry functions. The purpose of this article is to analyze the changes in Bulgarian agriculture which is characterized by great intensity and dynamics, as well as the dynamics in the development and specificity of land relations in Bulgaria in the context of the CAP. The methodical framework of this article provides a summary overview of the main changes in the agricultural policy and the structure of land relations in Bulgaria. A number of contemporary scientific quantitative and qualitative methods are used to achieve the intended objective set in this study: systematic and comparative analysis; monographic analysis; expert assessment. The results pointed out the fragmentation of the use of agricultural land, and the existence of a large number of small farms. In Bulgaria in recent years, extensive farming has been given a strong impetus at the expense of the intensive farming, a process that is of a sustainable nature and has a clear causal link. The agricultural sector has always been a strategic branch of Bulgarian economy.